Subwavelength lithography using metallic grating waveguide heterostructure - Yang, Xuefeng (2013)
We present subwavelength periodic gratings achieved by employing a metallic grating waveguide heterostructure (MGWHS). The mask can be designed to make one of its diffraction order (±mth) waves resonate with the surface plasmon wave supported by the MGWHS. With a finite-difference time-domain method, we numerically demonstrate that one-dimensional periodic structure of about 60 nm feature, which is far beyond the diffraction limit, can be patterned with the interference of the 3rd diffraction order waves of the mask at a wavelength of 546 nm. The technique can also be extended to two-dimensional patterns using circularly polarized incidence and for the incidence with an angle θ.